Synthesis and in vitro evaluation of potential antichagasic hydroxymethyinitrofurazone (NFOH-121): A new nitrofurazone prodrug - Chung, M. C.; Guido, RVC; Martinelli, T. F.; Goncalves, M. F.; Polli, M. C.; Botelho, KCA; Varanda, Eliana Aparecida [UNESP]; Colli, W.; Miranda, MTM; Ferreira, E. I. (Elsevier B.V., 2003)
The synthesis of mutual prodrugs of nitrofurazone with primaquine, using specific and nonspecific spacer groups, has been previously attempted seeking selective antichagasic agents. The intermediate reaction product, hydroxymethylnitrofurazone (NFOH-121), was isolated and tested in LLC-MK2 culture cells infected with trypomastigotes forms of Trypanosoma cruzi showing higher trypanocidal activity than nitrofurazone and benznidazol in all stages. The mutagenicity tests showed that the prodrug was less toxic than the parent drug. Degradation assays were carried out in pH 1.2 and 7.4. (C) 2003 Elsevier Ltd. All rights reserved.